The Experiences of Functioning and Health of Patients With Primary Sjögren's Syndrome: A Multicenter Qualitative European Study - Unger, Julia; Mattsson, Malin; Drăgoi, Răzvan G.; Avram, Claudiu; Boström, Carina; Buttgereit, Frank; Lackner, Angelika; Witte, Torsten; Raffeiner, Bernd; Peichl, Peter; Durechova, Martina; Hermann, Josef; et al. (Frontiers in Medicine, 2021)
Objective: To identify a spectrum of perspectives on functioning and health of patients with pSS from five European countries in order to reveal commonalities and insights in their experiences. Methods: A multicentre focus group study on patients with pSS about their perspectives of functioning and health was performed. Focus groups were chaired by trained moderators based on an interview guide, audiotaped and transcribed. After conducting a meaning condensation analysis of each focus group, we subsequently combined the extracted concepts from each country and mapped them to the International Classification of Functioning, Disability and Health. Results: Fifty-one patients with pSS participated in 12 focus groups. We identified a total of 82 concepts meaningful to people with pSS. Of these, 55 (67%) were mentioned by patients with pSS in at least four of five countries and 36 (44%) emerged in all five countries. Most concepts were assigned to the ICF components activities and participation (n=25, 30%), followed by 22 concepts (27%) that were considered to be not defineable or not covered by the ICF; 15 concepts (18%) linked to body structures and functions. Participants reported several limitations in daily life due to a mismatch between the capabilities of the person, the demands of the environment and the requirements of the activities. Conclusion: Concepts emerged in all five non-English speaking countries may be used to guide the development and adaption of patient-reported outcome measures and to enhance the provision of treatment options based on aspects meaningful to patients with pSS in clinical routine.